A multicenter study to assess the performance of the point-of-care RT-PCR Cobas SARS-CoV-2 & Influenza A/B nucleic acid test for use on the Cobas Liat system in comparison with centralized assays across healthcare facilities in the United States - Robbins, Elissa M.; Bertuzis, Rasa; Chiu, Ho-Chen; Miller, Lupe; Noutsios, Christopher (Journal of clinical microbiology, 2025)
This study highlights the benefits of RT-PCR point-of-care tests, namely comparable performance to centralized testing in multiple sample types and ease of use. Utilizing assays such as the POC Cobas SARS-CoV-2 & Influenza A/B test may improve the timely differentiation of respiratory diseases that share similar symptoms.